KDR gene polymorphisms and idiopathic recurrent spontaneous abortion. (16th November 2016) - Honarvar, Negar; Sheikhha, Mohammad Hasan; Farashahi Yazd, Ehsan; Pashaiefar, Hossein; Mohtaram, Shirin; Sazegari, Ali; Feizollahi, Zahra; Ghasemi, Nasrin
Abstract: Objective : Process of angiogenesis is essential for successful gestation. Disruption in this pathway leads to various undesirable consequences in pregnancy such as recurrent spontaneous abortion (RSA). One of the most important genes involved in angiogenesis is kinase-insert domain-containing receptor (KDR ). This study aimed to investigate the associations between two single-nucleotide polymorphisms (SNPs) of KDR gene, 1719A > T and 1192G > A, with idiopathic RSA in south-east Iran. Methods : A total of 230 women, including 110 women with a history of at least two consecutive spontaneous miscarriages and 120 healthy women were recruited in this study. Genomic DNA was extracted from peripheral blood samples of participants using the Salting out method. The KDR 1719A > T and 1192G > A polymorphisms were genotyped by the standard amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) technique. Results : For the case group, frequencies of 2.73%, 30% and 67.27% were observed for AA, AT and TT genotypes in1719A > T SNP, respectively, and the genotype frequencies for controls were equal to AA = 3.33%, AT = 32.5% and TT = 64.17%. Distribution of genotypes in 1192G > A SNP in the case group was 79.1%, 19.1% and 1.8% for GG, AG and AA, respectively, whereas the corresponding values for the controls were GG = 80%, AG = 20% and AA = 0. No significant difference was found between the case and control groups based on the frequency of KDR gene polymorphisms with the susceptibility to RSA. Conclusions : There is no association between these two SNPs of KDR gene and the susceptibility to RSA in women from south-east Iran.